Inequity Aversion and Individual Behavior in Public Good Games: An Experimental Investigation - Astrid Dannenberg; Thomas Riechmann; Bodo Sturm; Carsten Vogt (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
We present a simple two-steps procedure for a within-subject test of the inequity aversion model of Fehr and Schmidt (1999). In the first step, subjects played modified ultimatum and dictator games and were classified according to their preferences. In the second step, subjects with specific preferences according to the Fehr and Schmidt model were matched into pairs and interacted with each other in a standard public good game and a public good game with punishment possibility. Our results show that the specific composition of groups significantly influences the subjects' performance in the public good games. We identify the aversion against advantageous inequity and the information about the coplayer's type as the main influencing factors for the behavior of subjects.
More recent version: http://hdl.handle.net/10419/24620
Keywords: H41; C92; C91; 330; individual preferences; inequity aversion; experimental economics; public goods